Volume 3: Design and Analysis 2008
DOI: 10.1115/pvp2008-61726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-Conforming Thread Root Radius on the Fatigue Performance of Preloaded Threaded Fasteners

Abstract: This paper presents an experimental investigation of the effect of thread root non-conformance on the fatigue performance of preloaded M12×1.5 Class 10.9 fasteners. Thread roots were dimensionally inspected using optical methods in accordance with the DIN 933 specification. Axial load fatigue tests were performed in accordance with ISO 3800. Each bolt specimen was subjected to a fixed stress amplitude of 42 MPa above and below various levels of the mean tensile stress. Test data was analyzed and fracture surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[2,3,6].The factor that has the greatest influence on the mechanical properties and service performance of threaded components is the geometry and dimensional accuracy of the thread [2].Dong [2] and Leon [7] studied the influence of thread dimensional conformance on the selfloosening resistance and static strength of the threaded connection which will be greatly reduced due to the unqualified outer diameter, middle diameter or inner diameter of bolts and nuts. Nassar et al [8] showed that unqualified thread root radius will adversely affect the fatigue performance of pre-tightened threaded fasteners. In order to ensure the quality of thread, the thread quality inspection standard involves 11 main thread characteristics, and RPDD is one of them.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,6].The factor that has the greatest influence on the mechanical properties and service performance of threaded components is the geometry and dimensional accuracy of the thread [2].Dong [2] and Leon [7] studied the influence of thread dimensional conformance on the selfloosening resistance and static strength of the threaded connection which will be greatly reduced due to the unqualified outer diameter, middle diameter or inner diameter of bolts and nuts. Nassar et al [8] showed that unqualified thread root radius will adversely affect the fatigue performance of pre-tightened threaded fasteners. In order to ensure the quality of thread, the thread quality inspection standard involves 11 main thread characteristics, and RPDD is one of them.…”
Section: Introductionmentioning
confidence: 99%